Association of genetic markers with cardiomyopathy - Karthik, A.; Ramesh, M.; GeethaKumari, Konathala; Sudhakar, G. (International Journal of Research in Medical Sciences, 2017)
Background: Cardiomyopathy is an anatomic and pathologic diagnosis associated with muscle or electrical dysfunction of the heart. Cardiomyopathies represent a heterogeneous group of diseases that often lead to progressive heart failure with significant morbidity and mortality. Cardiomyopathy and myocarditis resulted in 443,000 deaths in 2013 up from 294,000 in 1990. Objective: The main objective of the present study is to observe the association of cardiomyopathy and genetic markers such as red cell enzymes namely, Esterase D [ESD] and Super oxide dismutase [SOD] and plasma proteins namely, Haptoglobin [HP] and Group specific component [GC] systems. Methods: In the present study, fifty cases presenting cardiomyopathy and fifty cases of age and sex matched healthy controls were included. Red cell enzymes were determined by standard agarose gel electrophoresis. Plasma samples were typed using PAGE electrophoresis. The statistical significance of differences between patients and controls were tested. Analysis of the data was carried out using Epi Info 5 software. Relative risk was calculated by the random-effects method. For odds ratio, confidence interval was calculated. The significance level was 5%. Results: The inter group heterogeneity for ESD and SOD of red cell enzymes and GC system of plasma proteins was found to be a significant value (ESD: χ2 =10.2564; d.f. = 2; 0.01>p>0.001; SOD: χ2 = 11.1120; d.f. = 2; 0.01>p>0.001; GC: χ2 = 15.5044; d.f. = 2; p>0.001), when observed between cardiomyopathy patients and controls. Thus, all the examined groups were deviating from Hardy-Weinberg equilibrium indicating a significant association between cardiomyopathy and these red cell enzymes and plasma protein markers. There was a predominant occurrence of Haptoglobin 2 phenotype in patients when compared to controls. Risk estimates show significant association with both ESD and GC systems with an increased risk of 100% and more, indicating that individuals with ESD (2-2 and 2-1) and GC (2-1) phenotypes are more likely to get the disease when compared with the other phenotypes of the ESD and GC systems. Conclusions: Out of seven genetic markers, four markers (ESD, SOD, HP and GC) are found to be significant i.e. they show some relation with the cardiomyopathy which influences the disease. Furthermore studies on genetic markers, to be attempted in future, would certainly enlighten us to assess the role of these polymorphic systems in different cardiomyopathies.